Effect of the Interaction between Elevated Carbon Dioxide and Iron Limitation on Proteomic Profiling of Soybean - Soares, José C.; Osório, Hugo; Pintado, Manuela; Vasconcelos, Marta W. (International journal of molecular sciences, 2022)
Elevated atmospheric CO2 (eCO2) and iron (Fe) availability are important factors affecting plant growth that may impact the proteomic profile of crop plants. In this study, soybean plants treated under Fe-limited (0.5 mM) and Fe-sufficient (20 mM) conditions were grown at ambient (400 μmol mol−1) and eCO2 (800 μmol mol−1) in hydroponic solutions. Elevated CO2 increased biomass from 2.14 to 3.14 g plant−1 and from 1.18 to 2.91 g plant−1 under Fe-sufficient and Fe-limited conditions, respectively, but did not affect leaf photosynthesis. Sugar concentration increased from 10.92 to 26.17 μmol g FW−1 in roots of Fe-sufficient plants and from 8.75 to 19.89 μmol g FW−1 of Fe-limited plants after exposure to eCO2. In leaves, sugar concentration increased from 33.62 to 52.22 μmol g FW−1 and from 34.80 to 46.70 μmol g FW−1 in Fe-sufficient and Fe-limited conditions, respectively, under eCO2. However, Fe-limitation decreases photosynthesis and biomass. Pathway enrichment analysis showed that cell wall organization, glutathione metabolism, photosynthesis, stress-related proteins, and biosynthesis of secondary compounds changed in root tissues to cope with Fe-stress. Moreover, under eCO2, at sufficient or limited Fe supply, it was shown an increase in the abundance of proteins involved in glycolysis, starch and sucrose metabolism, biosynthesis of plant hormones gibberellins, and decreased levels of protein biosynthesis. Our results revealed that proteins and metabolic pathways related to Fe-limitation changed the effects of eCO2 and negatively impacted soybean production.